Timothy I Defending the Cross against Jews and Muslims: a Newly Discovered Testimony - Minov, Sergey (Medieval encounters, 2025)
The article presents for the first time the Syriac text, an English translation and discussion of the surviving fragments of a newly discovered apologetic composition by Timothy I (fl. 780–823), the East Syrian patriarch of Baghdad. In this work, the catholicos defends Christian practice of veneration of the cross against possible critique by Jewish and Muslim adversaries. Discussed in the context of Timothy’s other works and of the earlier and contemporary polemical literature by Christians, the newly published material offers a valuable evidence on the development of the repertoire of anti-Jewish and anti-Muslim polemical arguments among Syriac and Arab Christians during the eighth and ninth centuries.